The ability to kneel before and after total knee arthroplasty: the role of the pattern of osteoarthritis and the position of the femoral component. (1st September 2021) - Scott, Chloe E. H.; Holland, George; Gillespie, Matthew; Keenan, Oisin J.; Gherman, Anda; MacDonald, Deborah J.; Simpson, A. Hamish R. W.; Clement, Nicholas D.
Abstract : Aims: The aims of this study were to investigate the ability to kneel after total knee arthroplasty (TKA) without patellar resurfacing, and its effect on patient-reported outcome measures (PROMs). Secondary aims included identifying which kneeling positions were most important to patients, and the influence of radiological parameters on the ability to kneel before and after TKA. Methods: This prospective longitudinal study involved 209 patients who underwent single radius cruciate-retaining TKA without patellar resurfacing. Preoperative EuroQol five-dimension questionnaire (EQ-5D), Oxford Knee Score (OKS), and the ability to achieve four kneeling positions were assessed including a single leg kneel, a double leg kneel, a high-flexion kneel, and a praying position. The severity of radiological osteoarthritis (OA) was graded and the pattern of OA was recorded intraoperatively. The flexion of the femoral component, posterior condylar offset, and anterior femoral offset were measured radiologically. At two to four years postoperatively, 151 patients with a mean age of 70.0 years (SD 9.44) were included. Their mean BMI was 30.4 kg/m 2 (SD 5.36) and 60 were male (40%). They completed EQ-5D, OKS, and Kujala scores, assessments of the ability to kneel, and a visual analogue scale for anterior knee pain and satisfaction. Results: The ability to kneel in the four positions improved in between 29 (19%) and 53 patients (35%) after TKA, but declined in between 35 (23%) and 46 patients (30%). Single-leg kneeling was most important to patients. After TKA, 62 patients (41%) were unable to achieve a single-leg kneel, 76 (50%) were unable to achieve a double-leg kneel, 102 (68%) were unable to achieve a high-flexion kneel and 61 (40%) were unable to achieve a praying position. Posterolateral cartilage loss significantly affected preoperative deep flexion kneeling (p = 0.019). A postoperative inability to kneel was significantly associated with worse OKS, Kujala scores, and satisfaction (p < 0.05). Multivariable regression analysis identified significant independent associations with the ability to kneel after TKA (p < 0.05): better preoperative EQ-5D and flexion of the femoral component for single-leg kneeling; the ability to achieve it preoperatively and flexion of the femoral component for double-leg kneeling; male sex for high-flexion kneeling; and the ability to achieve it preoperatively, anterior femoral offset, and patellar cartilage loss for the praying position. Conclusion: The ability to kneel was important to patients and significantly influenced knee-specific PROMs, but was poorly restored by TKA with equal chances of improvement or decline. Cite this article: Bone Joint J  2021;103-B(9):1514–1525.